Exploring the role of Perpustakaan Sultan Badlishah to inculcate reading habit among students / Siti Fatihah Yacob - Yacob, Siti Fatihah (Faculty of Information Management, 2011)
This study aims to study observe on the role of the Perpustakaan Sultan Badlishah (PSB) inculcate the students interest on reading habit. The respondents of this study focus on BIS students in UiTM, Kedah which consist of 245 students and average most of their age around 19-26 years old. The problem statement has stated that when nowadays there is a trend that students come to the library not to read the book but to do that something else such as doing their work or make discussion among students. In fact, the reading interest and habits of Malaysians is very low hence there is the role of library to inculcate reading habit among students. This study used research objective, research question and literature review. There are three independent variables had been discussing in this research which are collection, environment, and activities. For the methods this study used questionnaires to collected data and the SPSS (Statistical Package for the Social Science) to analysed the data.